Penggunaan Energi pada Usahatani Padi di Lahan Lebak - Sudirman Umar; Noorginayuwati Noorginayuwati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2005)
One of the main purposes in Agricultural development in Indonesia is increasing food stability. So many efforts have been done to achieve high rice production but the energy consumption and its distribution has not been analyzed yet. Hence, analyzing on distribution of energy consumptions through energy analysis and cost are needed to be done. The research was conducted in September to December 2004 in Hamayung Utara and Baruh Kembang village, Daha Utara district South Hulu Sungai, Province of South Kalimantan, as the center of monotonous swamplands (lebak) rice production. The result showed that energy input of rice cultivation in swampy land using pump technology in it production process, input energy up to 50 MJ/ha, unless in seedling stage 17.54 MJ/ha. Total energy consumption during production process was 8427,37 MI/ha but using traditional method without pump was 559,08 MJ/ha. Cost input analysis showed that cost input using pump technology as much as Rp. 2,710.019.00/ha and 36.29% lower than the income of the cost output. Energy input using pump technology is much lower (16.06%) compared to energy output 52,449.6 MJ/ha. Addition with irrigation technology and chemical energy input (chemical fertilizer) increased cost output as much as Rp. 2,841,250.00 equal output energy 33,413.10 MJ/ha and increased energy output as much as 175,52 %. On farming system in monotonous swampy land the energy input ang production increased 14.07 and 1.75 times by addition machinery technology (pump).